Domestic wastewater nutrients removal using GAC and limestone by physico-chemical treatment - Hussain, S.; Aziz, H.A.; Isa, M.H.; Asaari, F.A.H.; Adlan, M.N. (2006)
The present study was conducted to investigate the removal of wastewater nutrients (ammoniacal nitrogen, NH4-N and orthophosphate, PO4-P) using limestone (LS) and granular activated carbon (GAC) by physico-chemical method. In preliminary batch experiments, optimum shaking and settling times were determined as 150 minutes and 120 minutes, respectively. Limestone alone was not efficient in the removal of NH4-N (12%) however it contributed to 91% removal of PO4-P. The LS-GAC mixture ratio of 25:15 removed about 58% NH4-N and 93% PO4-P. Lower initial concentration of adsorbate and increase in adsorbent dosage yielded higher removal and adsorption capacity. The equilibrium adsorption data followed Freundlich isotherm (R2 > 0.98), however it showed weak bonding. The column study showed that lower flowrate resulted in longer column saturation time. The column saturation time for NH4-N at pH 7 was much longer than pH 4 because at pH 4 ammonia was largely in ionized (NH4+) form and was removed by adsorption but at pH 7 a substantial part of it was also in the molecular (NH3) form which was subject to gradual removal by stripping. The mixture (LS-GAC) showed higher adsorption capacity of phosphate at pH 4 compared to pH 7 and pH 11. Limestone also behaved as an acid neutralizing media which increased the final effluent pH from 4 to the range of 8.24 to 8.41. It was concluded that the usage of GAC can be reduced by combining GAC with LS for the removal of NH4-N and PO4-P from wastewater, thus reducing the cost of treatment.